Cold Compresses in Overcoming First Stage Labor Pain at PMB Andina - Deby Utami Siska Ariani (Lembaga Pengembangan Kinerja Dosen, 2024)
On average, 85-90% of pregnant women in Indonesia experience severe labor pain and 7-15% of those who do not experience labor pain. Labor pain results in increased activity of the sympathetic nervous system which causes an increase in blood pressure, pulse rate, respiration, nausea, vomiting, and diaphoresis. Data shows that 15% of mothers in Indonesia experience birth complications and 21% are caused by experiencing very severe pain. The aim of the research was to analyze the effect of cold compresses on first stage labor pain. The research design used a quasi-experimental one group pre-posttest. The population, namely all mothers giving birth at PMB Andina in May 2024, totaled 30 respondents. The sampling technique uses total sampling. Statistical tests use the Wilcoxon test. The research results obtained were that the average labor pain before the cold compress was 5.13 and the average labor pain after the cold compress was 4.00, meaning there was a decrease in the level of pain by 1.13. The significant value was found to be p: 0.001 < 0.05, meaning that there was an effect of cold compresses on labor pain in mothers giving birth at PMB Andina Palembang. It is hoped that health workers can improve maternal care during childbirth, one of which is by providing complementary services in the form of cold compresses.